Research on the new media communication channels of the intangible cultural heritage "Puppet Show" - Ge, Wenbo (Transactions on Economics, Business and Management Research, 2024)
Puppetry, an intangible cultural heritage with profound cultural significance, has experienced film and media innovations in the 20th century by Taiwan’s Perak Puppetry Company and attempted to break through the barriers of communication. However, it has not fundamentally changed its niche communication status, still being limited to circulation within specific circles. This reflects the challenges that intangible cultural heritage faces in the new media era: relying solely on film and TV transformation is not enough to rejuvenate, and deeper strategic exploration and practical innovation are required. In the context of the new media era, the rapid development of the wireless communication technology has led society into a fast-paced lifestyle, and the communication methods of traditional intangible cultural heritage have encountered unprecedented bottlenecks. In response to this situation, this article aims to explore new directions for the dissemination of intangible cultural heritage by analyzing the intangible cultural heritage represented by puppetry and exploring how to effectively utilize the broad reach and instant interaction characteristics of new media. Overcoming communication barriers can make this precious cultural wealth accumulated in history shine once more, attract the attention of more modern audiences, and promote its inheritance and promotion in contemporary society.